Donor-derived TB after kidney transplantation: a case report - Ulisses,Luiz Roberto de Sousa (2022)
Abstract Introduction: Tuberculosis (TB) is a possible serious complication of solid organ transplantation, associated with high mortality and morbidity. Post-transplant TB has varied pathogenesis with many approaches to its prevention, which is the most important way to reduce its incidence. Treatment of TB in organ recipients is challenging because of drug toxicity and interaction with immunosuppressants. Case report: an 18-year-old woman that underwent kidney transplantation from a deceased donor and was discharged with fair renal function was readmitted at 37th postoperative day with fever. CT showed signs of miliary TB and fluid collection besides graft fistulization through the skin. The patient presented positive BAAR in the drained fluid and Koch's bacillus in the urine. She was treated with a four-drug regimen (rifampicin, isoniazid, pyrazinamide, and etambutol), with great response and preserved graft function. We were informed that the recipient of the contralateral kidney also presented post-transplant TB, implying in a donor-derived origin. Conclusion: TB is an important differential diagnosis for infectious complications in patients after solid-organ transplantation, especially in endemic regions. Its initial clinical presentation can be unspecific and it should be suspected in the presence of fever or formation of fluid collections. The suspicion of TB is the key to early diagnosis and satisfactory outcomes in post-transplant TB.